MAGMATIC FRACTIONATION OF HF AND W: CONSTRAINTS ON THE TIMING OF CORE FORMATION AND DIFFERENTIATION IN THE MOON AND MARS - Righter K.; Shearer C.K. (My University, 2003)
Excesses of 182W have previously been measured in samples from the Moon and Mars, and can be derived from high Hf/W regions in their interiors during their early histories. Although planetary mantles will have superchondritic Hf/W after core formation, the extent to which high Hf/W regions could be generated by magmatic fractionation has not been evaluated. In order to address the latter possibility, we have carried out experiments from 100 MPa to 10.0 GPa, 1150 to 1850°C, at oxygen fugacities near the IW (iron-wustite) buffer, and measured partition coefficients for W and Hf for plagioclase-liquid, olivine-liquid, orthopyroxene-liquid, clinopyroxene-liquid, garnet-liquid, and metal-liquid pairs. Clinopyroxene and garnet are both capable of fractionating Hf from W during magmatic crystallization or mantle melting, and minor variations in the measured D's can be attributed to crystal chemical effects. Excesses of 182W and 142Nd in lunar samples can be explained by fractionation of Hf from W, and Sm from Nd (by ilmenite and clinopyroxene) during crystallization of the latest stages of a lunar magma ocean. Correlations of #W with #Nd in martian samples could be a result of early silicate fractionation in the martian mantle (clinopyroxene and/or garnet).